Formulation and Evaluation of Darifenacin Hydrobromide Extended Release Dosage Form using Multiparticulate Drug Delivery System - Prabhakar Reddy Veerareddy, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Formulation and Evaluation of Darifenacin Hydrobromide Extended Release Dosage Form using Multiparticulate Drug Delivery System